Olfactory Ensheathing Cells: A Trojan Horse for Glioma Gene Therapy. (25th September 2018) - Carvalho, Litia A; Teng, Jian; Fleming, Renata L; Tabet, Elie I; Zinter, Max; de Melo Reis, Ricardo A; Tannous, Bakhos A
Abstract: Background: The olfactory ensheathing cells (OECs) migrate from the peripheral nervous system to the central nervous system (CNS), a critical process for the development of the olfactory system and axonal extension after injury in neural regeneration. Because of their ability to migrate to the injury site and anti-inflammatory properties, OECs were tested against different neurological pathologies, but were never studied in the context of cancer. Here, we evaluated OEC tropism to gliomas and their potential as a "Trojan horse" to deliver therapeutic transgenes through the nasal pathway, their natural route to CNS. Methods: OECs were purified from the mouse olfactory bulb and engineered to express a fusion protein between cytosine deaminase and uracil phosphoribosyltransferase (CU), which convert the prodrug 5-fluorocytosine (5-FC) into cytotoxic metabolite 5-fluorouracil, leading to a bystander killing of tumor cells. These cells were injected into the nasal cavity of mice bearing glioblastoma tumors and OEC-mediated gene therapy was monitored by bioluminescence imaging and confirmed with survival and ex vivo histological analysis. All statistical tests were two-sided. Results: OECs migrated from the nasal pathway to the primary glioma site, tracked infiltrative glioma stemlike cells, and delivered therapeutic transgene, leading to a slower tumor growth and increased mice survival. At day 28, bioluminescence imaging revealed that mice treated with a single injection of OEC-expressing CU and 5-FC had tumor-associated photons (mean [SD]) of 1.08E + 08 [9.7E + 07] vs 4.1E + 08 [2.3E + 08] for control group ( P  < .001), with a median survival of 41 days vs 34 days, respectively (ratio = 0.8293, 95% confidence interval = 0.4323 to 1.226, P   <   .001) (n = 9 mice per group). Conclusions: We show for the first time that autologous transplantation of OECs can target and deliver therapeutic transgenes to brain tumors upon intranasal delivery, the natural route of OECs to the CNS, which could be extended to other types of cancer.